Analisis Prediksi Kebangkrutan Menggunakan Model Altman Z-Score dan Zmijewski pada Perusahaan Multifinance - I Made Karya Utama; I Wayan Dodit Astawa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Bankruptcy is a problem that companies must be aware of. If the company experiences bankruptcy, then the company is experiencing business failure. One of the ways that companies do to detect and prevent this from happening is by monitoring financial performance using financial statement analysis. To be able to predict company bankruptcy usually uses several different models, in this study using the Altman and Zmijewski models. The purpose of this study was to analyze the prediction of bankruptcy in multifinance sector companies using the Altman and Zmijewski models. The data used in this study are secondary data in the form of company financial reports published on the Indonesia Stock Exchange website. The population in this study were all multifinance companies listed on the IDX, totaling 14 companies. The samples used in this study amounted to 14 companies using the census method or total sampling. The results of this study indicate that there are multifinance sector companies that are predicted to go bankrupt using the Altman Z-Score Model, there are multifinance sector companies that are predicted to go bankrupt using the Zmijewski Model, and there are significant differences between the Altman Z-Score Model and the Zmijewski Model in predicting bankruptcy in multifinance sector companies.